Argentine Argyrotaenia (Lepidoptera: Tortricidae): Synopsis and descriptions of two new species - Trematerra, Pasquale; Brown, John W. (Zootaxa, 2004)
We present descriptions, redescriptions, and/or diagnoses of the four species of Argyrotaenia reported from Argentina: A. pomililiana, new species, from Neuqu n and Buenos Aires provinces; A. tucumana, new species, from Tucum n; A. loxonephes (Meyrick), apparently endemic to Argentina; and A. sphaleropa (Meyrick) and its junior synonym, A. fletcheriella (K hler), a widespread species of the New World tropics. We provide images of the adults and illustrations of the male and female genitalia. We also present host records from an unpublished manuscript by the noted Argentine lepidopterist, Jos A. Pastrana. We briefly discuss the previous erroneous report of A. citrana (Fernald) from South America.